Feedback on audit and action planning for dental caries control: a qualitative study to investigate the acceptability among interdisciplinary pediatric dental care teams - Cunha-Cruz, Joana; Hilgert, Juliana Balbinot; Harter, Catherine; Rothen, Marilynn L.; Hort, Kim; Mallott, Elizabeth (Frontiers in Oral Health, 2023)
Introduction American Indian and Alaska Native children suffer from the poorest oral health of all populational groups in the United States. Evidence-based practices (EBP) for caries control are well established, but systematically implementing such practices have proven difficult. Audit and feedback with goal setting, and action planning to implement these EBPs have not been tested or adapted for Alaska Native healthcare settings. The aim of this study was to investigate acceptability and perceived feasibility of an audit and feedback intervention for pediatric dental caries control among dental providers and patient stakeholders. Methods The pilot program was implemented in two dental clinics from a tribal healthcare consortium in Alaska. Key-informant interviews were conducted to investigate the contextual, organizational, and behavioral facilitators and barriers to the implementation and expansion of the program. Interview transcripts were analyzed by two researchers using thematic analysis. Results Eight key informants were interviewed twice (during and after the intervention period), and one once, for a total of 17 interviews. Patient stakeholders were not interviewed due to COVID-19 pandemic clinic closures and social isolation mandates. Three principal themes emerged: a positive organizational climate and culture fostered the acceptability of the program, the positive impacts of the program observed in the pediatric dental teams and the organization, and the challenges to implement the program including understanding the data reports, trusting the accuracy of the data, and competing priorities. Conclusions The intervention of audit and feedback with goal setting and action planning was well accepted and perceived as feasible by the study participants given the financial and human resources provided by the research project. This qualitative study can inform the design and evaluation of process-oriented implementation strategies geared towards decreasing health inequities and improving health outcomes, such as dental caries in American Indian and Alaska Native children and adolescents.